Long-lived Charge-Transfer States in 9-Aryl-Acridinium Ions; A Critical Reinvestigation - Jan W. Verhoeven; Hendrik J. van Ramesdonk; Hong Zhang; Michiel M. Groeneveld; Andrew C. Benniston; Anthony Harriman (International Journal of Photoenergy)
In the recent literature a simple 9-aryl-acridinium ion was claimed to undergo an intramolecular, photoinduced charge shift to produce an extremely long-lived and very high energy charge-transfer state. The possible consequences of this observation are discussed and the tenability of the claims made is investigated via time resolved spectroscopy of a closely related system with spectroscopic characteristics allowing more solid identification of the actual photophysical events taking place. From the results obtained it appears likely that the long-lived species observed earlier in solution cannot be charge transfer in nature but must instead be identified as the lowest triplet state of the acridinium chromophore.